A process centred perspective of the creative industries : an analytical model for management - Lima, Fernando Afonso Carrapatoso (2015)
This dissertation adopts a process-centred perspective of understanding the economic model of the creative industries, so as to explore how can one build an analytical model that can be useful for improving management practices in those industries. The point of departure to address the research question was to review the debate around the definition of creative industries; then followed a discussion on the development of a framework for the understanding of the creative industries process-centred perspective; finally an assessment of the creative industries’ economic model from the management perspective was done via a value-chain analysis, in order to discuss the implications of the process-centred perspective for management and for public policy design. The research developed allowed the proposal of an analytical model that revealed the importance of operationalizing the understanding of value-creation through creativity in management practices. It also emphasized the challenge in balancing open-ended processes with the firm’s commercial purposes, by managing intangible aspects of the creative process and the engagement of the creative workers into the creative process. The analytical model developed may be helpful for managers insofar as it offers a disaggregation of the companies’ activities by focusing on the assessment of how the creative process can recursively occur in the company as a production process. Moreover it may help on the identification of the core-activities and the assessment of the main components of those activities. The research done intends to contribute to the understanding of how the creative industries work and to the development of good management practices in the sector. Thus, it also suggests that it would be interesting to develop research on a theoretical revision of the components of the creative industries’ economic model and on a proper comparative analysis of the model delivered at an inter-sector, an inter-temporal and at a subsector level. By advancing an analytical model for creative industries that is focused on its usefulness for management, it indicates areas of interest for empirical research.